Prosedur Kepabeanan, Imigrasi dan Karantina dalam Mendukung Penyelenggaraan Event MICE/ Event Internasional : Christina Lipuringtyas Rudatin - Wardhani, Annisa Wardhani; Rudatin, Christina Lipuringtyas Rudatin; Syah, Firman Syah (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
One of the most crucial aspects in organizing a MICE event is Customs, Immigration and Quarantine. Customs, Immigration and Quarantine activities are never separated from the implementation of MICE (Meeting, Incentive, Convention and Exhibition) events. Customs, Immigration and Quarantine activities play an important role in the sustainability of the implementation of MICE events both during pre, during and post events. The smoothness of Customs, Immigration and Quarantine procedures in organizing MICE events can be both an opportunity and a threat to the MICE industry. The implementation of Customs, Immigration and Quarantine activities that are measured and careful can be an opportunity for the bargaining position of the destination in the eyes of the world, the destination will have the opportunity to be re-elected as the host of the international MICE event because of the ease of Customs, Immigration and Quarantine procedures obtained by international participants / delegates. On the other hand, the implementation of Customs, Immigration and Quarantine activities that are not measured and not careful can be a threat to the destination if in its implementation there are procedural errors in the collection of import duties on goods, immigration procedures for delegates who attend or quarantine procedures for animals that will be included in the exhibition. This study aims to determine the role and procedures for handling Customs, Immigration and Quarantine in supporting the implementation of MICE events. The method used in this study is a qualitative method, data collection is carried out by literature studies and interviews. The analysis method used in this study is exploratory method.